Exploring the shape deformation of biomembrane tubes with theoretical analysis and computer simulation. Issue 44 (17th October 2016) - Liu, Xuejuan; Tian, Falin; Yue, Tongtao; Zhang, Xianren; Zhong, Chongli
Abstract : We show theoretically that different models for membrane tube deformations, that generate membrane pearling, buckling and bulging, can be classified into two categories: effective spontaneous curvature and membrane tension. Abstract : The shape deformation of membrane nanotubes is studied by a combination of theoretical analysis and molecular simulation. First we perform free energy analysis to demonstrate the effects of various factors on two ideal states for the pearling transition, and then we carry out dissipative particle dynamics simulations, through which various types of membrane tube deformation are found, including membrane pearling, buckling, and bulging. Different models for inducing tube deformation, including the osmotic pressure, area difference and spontaneous curvature models, are considered to investigate tubular instabilities. Combined with free energy analysis, our simulations show that the origin of the deformation of membrane tubes in different models can be classified into two categories: effective spontaneous curvature and membrane tension. We further demonstrate that for different models, a positive membrane tension is required for the pearling transition. Finally we show that different models can be coupled to effectively deform the membrane tube.